2019
DOI: 10.3390/cancers11081096
|View full text |Cite
|
Sign up to set email alerts
|

Role of the RAB7 Protein in Tumor Progression and Cisplatin Chemoresistance

Abstract: RAB7 is a small guanosine triphosphatase (GTPase) extensively studied as regulator of vesicular trafficking. Indeed, its role is fundamental in several steps of the late endocytic pathway, including endosome maturation, transport from early endosomes to late endosomes and lysosomes, clustering and fusion of late endosomes and lysosomes in the perinuclear region and lysosomal biogenesis. Besides endocytosis, RAB7 is important for a number of other cellular processes among which, autophagy, apoptosis, signaling,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 141 publications
(217 reference statements)
2
30
0
Order By: Relevance
“…A previous report by our group showed that RAB7A, a small GTPase and a master regulator of the late endocytic pathway, was able to modulate secretion of CD9-and CD81-positive exosomes [37]. The decreased expression of tetraspanin CD63 found in the present study may therefore be indicative of an altered late endocytic pathway [38], possibly suggesting disarrangements in late endocytic trafficking in PF&S.…”
Section: Discussionsupporting
confidence: 63%
“…A previous report by our group showed that RAB7A, a small GTPase and a master regulator of the late endocytic pathway, was able to modulate secretion of CD9-and CD81-positive exosomes [37]. The decreased expression of tetraspanin CD63 found in the present study may therefore be indicative of an altered late endocytic pathway [38], possibly suggesting disarrangements in late endocytic trafficking in PF&S.…”
Section: Discussionsupporting
confidence: 63%
“…One molecule that is essential for the degradation of EGFR and other receptors is RAB7, which is responsible for sorting them into late endosomes and lysosomes. In agreement with the effect observed after TMEM167A downregulation in gliomas cells, it has been shown that RAB7 is essential for AKT activation and signaling in other cancer cells [30]. Moreover, there is plenty of evidences supporting the existence of a tight regulation of the spatial and temporal compartmentalization of AKT activation and function [9].…”
Section: Discussionsupporting
confidence: 68%
“…RAB7 has also been associated with chemoresistance to cisplatin. Indeed, RAB7 was downregulated in cisplatin-resistant cervical cancer cell lines as compared to chemosensitive ones ( 107 ). Additionally, RAB7 overexpression induced chemosensitization of cisplatin-resistant cells, while depletion of RAB7 by siRNA induced resistance to cisplatin in chemosensitive cells ( 108 ).…”
Section: Impact Of Inhibiting Autophagosome-lysosome Fusion On the Rementioning
confidence: 99%